Wound Antiseptic Plants: An Overview of the Most Important Medicinal Plants in Iran Affecting Wound Infections - Mahnaz Mardani (Journal of Global Pharma Technology, 2017)
Surgical site infection refers to infection in surgical site which is created within 30 days after surgery. Infection may occur by bacteria, viruses, protozoa, fungi and worms. In traditional Iranian medicine, many plants are used to control and treat infections. Therefore, the present paper aims to recognize and introduce antiseptic medicinal herbs by which we can produce effective natural remedies for infection control. Medicinal herbs such as chamomile, flax, veneris, oleander, savory, mallow, castor, sage, garlic, harmala etc. are the most important medicinal plants for disinfecting wounds in Iran. Keywords: wound, infection, herbs, Iran